DIPLOMASI PERTAHANAN INDONESIA DALAM MENGHADAPI GRAY ZONE OPERATION CHINA COAST GUARD - Marcelino, Lucky; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
In August 2023, the Chinese government released its 2023 Standard Map, which unilaterally claims a significant portion of the North Natuna Sea. This claim overlaps with Indonesia’s Exclusive Economic Zone (EEZ) and has triggered a renewed escalation of maritime tensions. It also reinforces China’s Gray Zone Operations strategy, particularly through the China Coast Guard, thereby posing a threat to regional stability in Southeast Asia.This study analyzes Indonesia’s response using a soft power approach rooted in defense diplomacy to address the emerging threat. Employing a qualitative method and drawing on the theory of bandwagoning, the paper evaluates Indonesia’s defense diplomacy towards China through analysis of official documents, academic publications, and credible media sources. The findings indicate that Indonesia’s defense diplomacy in the North Natuna Sea emphasizes soft power mechanisms through bilateral cooperation under the 2007 Defence Cooperation Agreement (DCA), which includes officer exchanges, non-traditional military exercises, and intelligence sharing. This strategy has helped foster trust and crisis communication, particularly through forums such as Navy-to-Navy Talks. However, it has not directly addressed the gray zone tactics employed by the China Coast Guard. As an adaptive strategy, Indonesia’s soft power diplomacy requires reinforcement through a more responsive maritime policy to effectively counter non-conventional security threats. Keywords: Soft Power, Defence Diplomacy, Grey Zone Operation, China Coast Guard, Exclusive Economic Zone